2016
DOI: 10.1007/s00284-015-0978-4
|View full text |Cite
|
Sign up to set email alerts
|

Production and Biomedical Applications of Probiotic Biosurfactants

Abstract: Biosurfactants have been widely used for environmental and industrial applications. However, their use in medical field is still limited. Probiotic biosurfactants possess an immense antimicrobial, anti-adhesive, antitumor, and antibiofilm potential. Moreover, they have an additional advantage over conventional microbial surfactants because probiotics are an integral part of normal human microflora and their biosurfactants are innocuous to human. So, they can be effectively exploited for medicinal use. Present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 76 publications
0
29
0
5
Order By: Relevance
“…The present results with regard to lactose and protein content are lower than the results in the literature. Researchers mainly concentrated on Pseudomonas and Bacillus species for biosurfactant studies but recent papers revealed biosurfactants produced using lactic acid bacteria [1,4,7]. The potential of lactic acid bacteria regarding biosurfactant production is dependent on cultivation conditions (growth medium composition, temperature, growth phase of culture, aeration, agitation, and pH) and species [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present results with regard to lactose and protein content are lower than the results in the literature. Researchers mainly concentrated on Pseudomonas and Bacillus species for biosurfactant studies but recent papers revealed biosurfactants produced using lactic acid bacteria [1,4,7]. The potential of lactic acid bacteria regarding biosurfactant production is dependent on cultivation conditions (growth medium composition, temperature, growth phase of culture, aeration, agitation, and pH) and species [6].…”
Section: Discussionmentioning
confidence: 99%
“…According to the ring method, surface tension was determined by evaluating the surface tension of pure water (72 mN/m). An effective biosurfactant should decrease this value to 30 mN/m [1,5]. Various factors such as pH, salinity, and temperature that are effective on biosurfactant activity also affect the surface tension properties of the biosurfactant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Number of gut bacteria exceed the total number of host's eukaryotic cells and impart various health benefits. [15] This gut flora mainly consists of probiotic bacteria and migrates to other parts of body especially in breast of lactating females but the transport mechanism from gut to breast is still unknown. [16] Probiotics means "for life" or an antonym for antibiotics [17] , when taken in sufficient amount, viable and non-disease causing microorganisms (bacteria or yeasts) impart health benefits via preclusion (prevention) and cure of particular pathological disorders or can lessen the possibility of disease to host are referred as probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Most of these bacterial species reside in human intestine. [15] The only probiotic yeast employed is the nonpathogenic Saccharomyces boulardii. [22,23] LAB and certain non-LAB probiotics are generally recognized as safe organisms which can be securely used for medical or veterinary purpose.…”
Section: Introductionmentioning
confidence: 99%